2009
DOI: 10.1002/ajim.20786
|View full text |Cite
|
Sign up to set email alerts
|

Occupational immediate‐type asthma and rhinitis due to rhodium salts

Abstract: Rhodium salts should be considered as occupational immediate-type allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Nevertheless, allergic contact dermatitis caused by rhodium salts has been recently demonstrated in subjects working in jewelry trade (Goossens et al 2011) and one case of immediate-type asthma and rhinitis due to rhodium salts has been demonstrated in a electroplating plant worker (Merget et al 2010). Iavicoli et al (2012) demonstrated in vitro cell cycle arrest and DNA damage on fibroblasts treated with rhodium and iridium salts, with an earlier effect in rhodium treated cells.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, allergic contact dermatitis caused by rhodium salts has been recently demonstrated in subjects working in jewelry trade (Goossens et al 2011) and one case of immediate-type asthma and rhinitis due to rhodium salts has been demonstrated in a electroplating plant worker (Merget et al 2010). Iavicoli et al (2012) demonstrated in vitro cell cycle arrest and DNA damage on fibroblasts treated with rhodium and iridium salts, with an earlier effect in rhodium treated cells.…”
Section: Discussionmentioning
confidence: 98%
“…Since 2008 several case reports of occupational rhinitis caused by sensitizers, both high and low molecular weight (LMW) agents, seldom if ever described previously, have been published (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31]. In the majority of cases occupational rhinitis was associated with occupational asthma and atopy [20,[22][23][24][25][26][27][28][29][30].…”
Section: 'New' Agents Causing Occupational Rhinitismentioning
confidence: 99%
“…In the majority of cases occupational rhinitis was associated with occupational asthma and atopy [20,[22][23][24][25][26][27][28][29][30]. The diagnosis was based on work-related rhinitis symptoms, specific skin prick test (SPT) and inhalation challenges.…”
Section: 'New' Agents Causing Occupational Rhinitismentioning
confidence: 99%
“…Hairdressers and other beauty care professionals can develop occupational rhinitis after exposures to bleaching agents containing persulfate, oxidative hair dyes with paraphenylene diamine or toluene-2,5-diamine sulfate, and glues containing ethyl cyanoacrylate used to apply eyelash extensions [21][22][23]. In regards to metals, a 27-year-old male factory operator in an electroplating plant was reported to have developed occupational rhinitis secondary to his exposure to rhodium salts [24]. Finally, occupational rhinitis has been described in a nurse exposed to the hospital disinfectant chlorhexidine and separately in a pharmaceutical worker who was exposed to the medication sodium alendronate during packaging [25,26].…”
Section: Etiologic Agentsmentioning
confidence: 99%